Sensitivity of fish diel vertical migration depths to future changes in the Pacific Ocean oxygen minimum zone - Sam Ditkovsky; Laure Resplandy; Laureline Dalaut; Nicolas Barrier; Matthieu Lengaigne; Olivier Maury (Frontiers in Marine Science, 2026)
Diel vertical migrations in the ocean play a key role in predator-prey dynamics and the functioning of the biological carbon pump. However, changes in ocean conditions including warming and deoxygenation threaten to significantly perturb vertical migration patterns over the twenty-first century. Specifically, vertical migrations over regions of critically low oxygen, known as oxygen minimum zones (OMZs), are likely to be most sensitive to changes in temperature and oxygen. In this study, we apply a simplified prognostic ecosystem model (APECOSM-1D) to changing conditions in the Pacific Ocean OMZ as simulated by 13 Earth System Models from the Coupled Model Intercomparison Project Phase 6 (CMIP6). We find that modeled fish migration depths at a given location in the region may deepen or shoal by over 100 m by the end of the century; however, there are large uncertainties across the CMIP6 ensemble for the geographic pattern of migration depth changes. To reconcile this, we adopt a water mass based approach which aggregates changes into regions defined by their vertical oxygen minimum value. In this framework, we find that fish migration depths over the lowest oxygen core of the OMZ remain stable due to compensating changes in temperature and oxygen. Meanwhile, away from the OMZ core, ocean warming and deoxygenation together drive shallower migration depths in projected conditions.

Coastal Hypoxia in the Indian Ocean: Unraveling Drivers of Spatio‐Temporal Variability - Fan Yang; Laure Resplandy; Yangyang Zhao; Sam Ditkovsky (Global Change Biology, 2025)
Coastal hypoxia in the densely populated Indian Ocean regions has dramatic consequences for ecosystems and ecosystem services such as fisheries and coastal protection. However, inadequate understanding of the spatio‐temporal variability of coastal hypoxia in the region, and its physical and biological drivers, poses a major challenge for anticipating these risks. Here we use in‐situ observations and a high‐resolution (1/12 degree) biophysical model of the Indian Ocean to map areas with heightened vulnerability to coastal hypoxia and identify the drivers of coastal oxygen dynamics. We find strong regional disparities in the mechanisms and temporal scales that govern coastal hypoxia: seasonal upwelling in the eastern Arabian Sea, interannual upwelling/downwelling linked to Indian Ocean Dipole events in the eastern Bay of Bengal, intraseasonal fluctuations introduced by coastal currents, Kelvin waves, and eddies along the western Bay of Bengal, and biologically driven oxygen variations at the mouth of major rivers in the northern Bay of Bengal (e.g., Ganges–Brahmaputra and Irrawaddy–Sittang Deltas). This basin‐scale mapping identifies regions where intraseasonal hypoxia (e.g., western Bay of Bengal, river deltas) makes prediction of these events challenging and calls for intense monitoring, and regions where seasonal and interannual hypoxia (e.g., eastern Arabian Sea, eastern Bay of Bengal) facilitates the prevention of the adverse impacts on coastal ecosystems and their services.

Contemporary decline in northern Indian Ocean primary production offset by rising atmospheric nitrogen deposition - Manon Malsang; Laure Resplandy; Laurent Bopp; Yangyang Zhao; Sam Ditkovsky; Fan Yang; Fabien Paulot; Marina Lévy (Frontiers in Marine Science, 2024)
Since 1980, atmospheric pollutants in South Asia and India have dramatically increased in response to industrialization and agricultural development, enhancing the atmospheric deposition of anthropogenic nitrogen in the northern Indian Ocean and potentially promoting primary productivity. Concurrently, ocean warming has increased stratification and limited the supply of nutrients supporting primary productivity. Here, we examine the biogeochemical consequences of increasing anthropogenic atmospheric nitrogen deposition and contrast them with the counteracting effect of warming, using a regional ocean biogeochemical model of the northern Indian Ocean forced with atmospheric nitrogen deposition derived from an Earth System Model. Our results suggest that the 60% recent increase in anthropogenic nitrogen deposition over the northern Indian Ocean provided external reactive nitrogen that only weakly enhanced primary production (+10 mg C.m –2 .d –1 .yr –1 in regions of intense deposition) and secondary production (+4 mg C.m –2 .d –1 .yr –1 ). However, we find that locally this enhancement can significantly offset the declining trend in primary production over the last four decades in the central Arabian Sea and western Bay of Bengal, whose magnitude are up to -20 and -10 mg C.m –2 .d –1 .yr –1 respectively.